Curl-Up Test: A New Abdominal Muscular Endurance Test: 仰臥捲腹測試法: 測定腹肌耐力的新方法 - CHUNG, Pak Kwong (Asian Journal of Physical Education & Recreation, 1995)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Sit-up is a popular exercise for both athletes and health fitness participants. It is almost universally accepted as an effective training method of abdominal strength and endurance. The 1-minute timed sit-up (modified sit-up) test, modified from the straight-legged sit-up with hands locked behind the head, is widely used in the health fitness testing such as Physical Best of AAHPERD, National Children and Youth Fitness Study (NCYFS & NCYFS II) of the United States Department of Health and Human Services, and Survey of Health Related Fitness & Lifestyle of Working Population Aged 20-39 in Hong Kong conducted by Hong Kong Physical Fitness Association etc. Although the modified sit-up was assumed to be a safer test than the straight-legged sit-up, researchers are still not satisfied with it. Are there any problems with sit-up test? Is the curl-up test developed by Robertson and Magnusdottir (1987) safer and more valid and reliable than the modified sit-up test? All such queries are being discussed in this article.